Assessment of Uncertainties and Errors in Post-Chernobyl Dosimetry - Drozdovitch, Vladimir; Masiuk, Sergii; Kryuchkov, Victor; Minenko, Victor; Chizhov, Konstantin; Chepurny, Mykola; Kukhta, Tatiana; Golovanov, Ivan; Bakhanova, Elena; Chumak, Vadim (Radiation research, 2023)
The present paper reviews the uncertainties and errors in complex dosimetry systems that were developed to estimate individual doses in different post-Chernobyl (Chornobyl) radiation epidemiology studies among the general population and the cleanup workers. These uncertainties and errors are associated with (i) instrumental radiation measurements of humans and environmental samples, (ii) inherent uncertainties arising from the stochastic random variability of the parameters used in exposure assessment and from a lack of knowledge about the true values of the parameters, and (iii) human factor uncertainties due to poor memory recall resulting in incomplete, inaccurate, or missing responses during personal interview with study subjects conducted long after exposure. Relative measurement errors of 131I thyroid activity associated with devices for measuring radioactivity in the thyroid reached up to 0.86 (coefficient of variation). The inherent uncertainty in estimates of individual doses varied between different studies and exposure pathways (GSD from 1.2 to 15 for model-based doses and from 1.3 to 5.1 for measurement-based doses). The human factor uncertainties can cause individual doses to be underestimated or overestimated by an average of 10 times for model-based doses and 2 times for measurement-based doses calculated for the general population and up to 3 times for doses calculated for cleanup workers. The sources of errors and uncertainties, especially the human factor uncertainties, should be carefully considered in dose assessment for radiation epidemiological studies, with particular attention to studies involving persons without instrumental radiation measurements.